Respostas

  • Usuário do Brainly
2013-01-09T00:11:43-02:00

Fatorando os binômios dados, tém-se:

 

\text{a}^2+\text{a}\text{x}=\text{a}\cdot\text{a}+\text{a}\cdot\text{x}

 

\text{ay}+\text{xy}=\text{a}\cdot\text{y}+\text{x}\cdot\text{y}

 

 

Desta maneira, temos:

 

\text{mmc} \ (\text{a}^2+\text{ax}), (\text{ay}+\text{xy})=(\text{a}^2+\text{x})\cdot\text{y}=\text{a}^2\text{y}+\text{xy}

1 1 1
2013-01-09T02:07:48-02:00

a²+ax = a(a+x)

ay+xy = y(a+x)

 

Portanto, MMC = ay(a+x) = a²y + axy

1 1 1